SIFAT PENGGERGAJIAN DAN PEMESINAN ENAM JENIS KAYU HTI - Jamal Balfas; Osly Rachman Rachman (Jurnal Penelitian Hasil Hutan, 1989)
This paper  presented   the  result  of  study   on  sawing  and  machining  properties   of  six  Indonesian   wood  species  being developed   as raw  materials  for  the  wood   working   industries.   The  sawing  properties   studied   comprise   of  sawn  timber recovery,   sawing  velocity   and power   consumption.    Whereas  the  machining  properties   of  the  timber  were tested  according to  the  modified   ASTM D-1666   as described   in the  Forest  Products  Research  Institute   Report   No.   160  (1982).The   result  showed   that  all of  the  species  has good  sawn  timber  recovery,   i.e.  more  than 50%. Three of  them  can be cut  eastiy wilh  higher  sawing  velocity   and  lower  power  consumption    in comparison  with  the other  three.  The species  that have good or very good  machining  properties   is merkuyung   (Shorea johorensis).  Species  of  meranti  merah  (Shorea  fallax) has  relatively  poor   machining  properties.    Whereas  the  other  four  species  are good   in some  properties   and  fair  to poor in others.